Characterization of cowpea genotype resistance to Callosobruchus maculatus - Castro, Maria De Jesus Passos De [UNESP]; Baldin, Edson Luiz Lopes [UNESP]; Cruz, Patrícia Leite [UNESP]; Souza, Camila Moreira De [UNESP]; Silva, Paulo Roberto Arbex [UNESP] (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2013)
The objective of this work was to characterize the resistance of 50 cowpea (Vigna unguiculata) genotypes to Callosobruchus maculatus. A completely randomized design with five replicates per treatment (genotype) was used. No-choice tests were performed using the 50 cowpea genotypes to evaluate the preference for oviposition and the development of the weevil. The genotypes IT85 F-2687, MN05-841 B-49, MNC99-508-1, MNC99-510-8, TVu 1593, Canapuzinho-1-2, and Sanzi Sambili show non-preference-type resistance (oviposition and feeding). IT81 D-1045 Ereto and IT81 D-1045 Enramador exhibit antibiosis against C. maculatus and descend from resistant genitors, which grants them potential to be used in future crossings to obtain cowpea varieties with higher levels of resistance.

O objetivo deste trabalho foi caracterizar a resistência de 50 genótipos de feijão-caupi (Vigna unguiculata) a Callosobruchus maculatus. Utilizou-se o delineamento inteiramente casualizado com cinco repetições por tratamento (genótipo). Testes de confinamento foram realizados com os 50 genótipos de feijão-caupi, para avaliar a preferência para oviposição e o desenvolvimento do caruncho. Os genótipos IT85 F-2687, MN05-841 B-49, MNC99-508-1, MNC99-510-8, TVu 1593, Canapuzinho-1-2 e Sanzi Sambili apresentam resistência do tipo não preferência (oviposição e alimentação). IT81 D-1045 Ereto e IT81 D-1045 Enramador apresentam antibiose contra C. maculatus e descendem de genitores resistentes, o que lhes confere potencial para serem utilizados em futuros cruzamentos, para obtenção de variedades de feijão-caupi com maior nível de resistência.
Caracterização da resistência de genótipos de feijão-caupi a Callosobruchus maculatus
Keywords: Vigna unguiculata; Bruchinae; Chrysomelidae; resistência de plantas; armazenamento; Vigna unguiculata; Bruchinae; Chrysomelidae; plant resistance; storage